Knowledge, attitude, practice, and associated factors of physicians towards cardiopulmonary resuscitation at a tertiary hospital in Ethiopia - Natan Mulubrhan Alemseged; Gobena Tesfaye; Abera Admas (African Journal of Emergency Medicine)
Introduction: Cardiopulmonary resuscitation (CPR) is performed on victims of cardiac arrest. It is important for health professionals to successfully perform these lifesaving skills. This study aimed to assess the CPR knowledge, attitude, practice, and associated factors of physicians working at Hiwot Fana Comprehensive Specialized Hospital Eastern Ethiopia. Methods: An institutional-based cross-sectional study was implemented. A stratified random sampling technique was used. A self-administered questionnaire and a manikin was used to assess CPR skills. The results are presented in the text, tables, and graphs. Multivariate logistic regression was used to identify factors associated with levels of competency. The adjusted odds ratio with the corresponding 95 % confidence interval was calculated to show the strength of the association. Results: This study revealed that 63.7 % [95 % CI 57 % -71 %] of the physicians had good knowledge, and their overall competency in CPR was found to be 63 % [95 % CI 54 % - 72 %]. They have a positive attitude regarding the importance of CPR and a willingness to provide CPR. Physicians who took resuscitation training (adjusted odds ratio 11.8 [4.29–32.42]) and a specialist (adjusted odds ratio 7.99 [1.87–34.27]) were more competent than their counterparts. Discussion: The results demonstrate suboptimal CPR competency among physicians’ representatives at a tertiary hospital in Eastern Ethiopia. Taking CPR training and being a specialist were found to have an effect on being competent in CPR. Participants reported positive attitudes toward doing CPR. A system of regular, updated refresher training for physicians should be implemented to maintain CPR competencies. Hospitals should also be equipped with materials and drugs needed for CPR.